1947
DOI: 10.1111/j.2164-0947.1947.tb01283.x
|View full text |Cite
|
Sign up to set email alerts
|

SECTION OF BIOLOGY: Studies on the Pathologic Effects Produced by Two Analogues of Pyridoxine*

Abstract: Analogues of Pyridoxine." (This lecture was illustrated by lantern slides.)Although inhibitors and poisons have been used for a long time in the study of isolated enzyme systems, it has been only in relatively recent years that physiological studies have been made with specific metabolite antagonists. Compounds with chemical structures similar to vitamins, hormones, and amino acids have been prepared which antagonize or inhibit such metabolites.' The term, antivitamin, has been applied to those compounds which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1949
1949
1981
1981

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Ott (28) reported on the antipyridoxine activity of one of these antimetabolites, desoxypyridoxine, and found the inhibitory ratio to be 2: 1 in chicks. Mushett, Stebbins and Barton (29) have reported a study of pathologic changes resulting from growth reversal by this compound and found that these changes were similar to those found in pyridoxine deficient animals, the chick, puppies, and monkeys. Stoerk (30) reported that lymphosarcoma transplants failed to grow in mice on a pyridoxine deficient diet and that these implants regressed when mice were placed on a deficient diet and desoxypyridoxine was added to the regimen.…”
mentioning
confidence: 67%
“…Ott (28) reported on the antipyridoxine activity of one of these antimetabolites, desoxypyridoxine, and found the inhibitory ratio to be 2: 1 in chicks. Mushett, Stebbins and Barton (29) have reported a study of pathologic changes resulting from growth reversal by this compound and found that these changes were similar to those found in pyridoxine deficient animals, the chick, puppies, and monkeys. Stoerk (30) reported that lymphosarcoma transplants failed to grow in mice on a pyridoxine deficient diet and that these implants regressed when mice were placed on a deficient diet and desoxypyridoxine was added to the regimen.…”
mentioning
confidence: 67%
“…Effect of DesoxypyridoxineS.--Since desoxypyridoxine has been found to be a powerful inhibitor of the biological activity of pyridoxine in chicks (35,36), dogs and monkeys (35), and rats (38), it seemed possible that this vitamin analogue might have some influence on the susceptibility of mice to infections with PVM. In a preliminary experiment weanling mice after inoculation with PVM were fed a diet containing no pyridoxine (S-3) and were given desoxypyridoxine 2.0 mg. per 100 cc.…”
Section: Effect Of Varying Amounts Of Pyridoxine--in Order To Determine What Dosagementioning
confidence: 99%
“…so Desoxypyridoxine given to tryptophane-fed, pyridoxine-deficient rats caused an increased excretion of xanthurenic acid (121). The histological changes in tissues of chicks, monkeys, and dogs induced by desoxypyridoxine include an anemia and atrophy of spleen, lymph nodes, thymus gland, and the blood forming con- stituents of the bone marrow (122). Antibody responses were impaired and a marked atrophy of lymphoid tissue in rats and mice resulted from the administration of desoxypyri' doxine (123).…”
mentioning
confidence: 99%